Investigação da toxicidade pré-clínica e possíveis mecanismos de ação central do timol em camundongos: estudos neuroquímicos e participação do estresse oxidativo - Fernandes, Mariana Lima (2017)
Depression is the leading cause of health and disability problems throughout the world and is characterized as a non-communicable disease. According to the latest estimates by the World Health Organization (WHO), more than 300 million people live with depression. In the Americas, the number of people affected is about 50 millions of these are estimated to be 11 million Brazilians with this mental disorder, in which the individual presents a permanent sadness, loss of interest for pleasurable activities for weeks or more. Depression can also cause feelings of guilt, lack of self-esteem, sleep and appetite disorders, feeling tired and lack of concentration, in more severe cases can lead to suicide. In view of this, many studies have been developed in search of alternative or complementary treatments to the already existing ones, among them the studies with medicinal plants. Thymol (2-isopropyl-5-methyl-phenol) is a monoterpene extracted from the essential oil of various aromatic plants such as rosemary (Lippia sidoides). Through previous experimental studies, thymol showed an antidepressant effect in the forced swimming test and tail suspension when administered orally in male mice in single doses of 25 mg / kg and 50 mg / kg. In view of this, this study aimed to investigate the possible mechanisms of central thymol action in mice with neurochemical tests and the participation of oxidative stress. The results showed that in the evaluation of acute toxicity, thymol was classified as category 5 with low toxicity risk, did not present histological changes in organ analysis and in the evaluation of toxicity with repeated doses no significant alterations were found regarding the biochemical and hematological parameters. In the forced swim test, the effect on thymol-reduced immobility time was reversed by pre-treatment of animals with serotonergic receptor antagonists such as ritonavir and Ondansetron, since this effect was not evidenced in the presence of NAN-190, a 5HT1A receptor antagonist. An increase in monoamine levels was evidenced by HPLC, noradrenaline, dopamine, and especially serotonin and reduced their respective metabolites. It did not alter the amount of SOD, reduced catalase activity in the striatum, reduced MDA and nitrite levels and increased GSH levels in the brain areas studied and increased BDNF levels in the hippocampus. These results suggest that thymol offers low risks of toxicity, has antidepressant effects probably related to the systems: noradrenergic, dopaminergic and serotonergic suggesting the participation of the receptors 5HT2A / 2C and 5HT3, presents antioxidant properties and a possible neuroprotective effect.